Retroperitoneal metastatic poorly differentiated carcinoma with β-human chorionic gonadotropin secretion presenting as a psoas abscess: A case report and review of the literature. Issue 19 (May 2017) - Wang, Bingjin; Liu, Weifang; Shao, Zengwu; Zeng, Xianlin
Abstract: Rationale: Psoas abscesses generally arise from a contiguous intra-abdominal or pelvic infectious process or hematogenous spreading of bacteria. The serum β-human chorionic gonadotropin has been used to detect normal or ectopic pregnancy. It also can be utilized in following up carcinomas. Patient concerns: Here, we reported a case of a 47-year-old woman who presented with a left psoas mass presumptively diagnosed as an abscess secondary to lumbar tuberculosis In addition, the patient had abnormal increase of β-human chorionic gonadotropin. The computed tomography (CT) scan and magnetic resonance imaging (MRI) showed that the 5th lumbar vertebral infection or tuberculosis with left psoas abscess. CT-guided percutaneous biopsy, surgical exploration and biopsy, and 18 F-FDG (fluorodeoxyglucose) positron emission tomography-CT (PET-CT) were used to make a definite diagnosis. The sigmoidoscopy and biopsy were used to further diagnose. Diagnoses: The biopsy of left psoas demonstrated metastatic or infiltrating poorly differentiated carcinoma with secretion of β-human chorionic gonadotropin. The subsequent pathological examination of neoplasm showed the same pathologic morphology. Interventions: Appropriate treatment of infected retroperitoneal mass, systematic chemotherapy and cancer biotherapy for metastatic poorly differentiated carcinoma were taken. Outcomes: Interventions provided little help until the patient died of secondary infection and multiple organ failure. Lessons: This case represents an extremely unusual clinical presentation of metastatic poorly differentiated carcinoma with secretion of β-human chorionic gonadotropin presenting as a psoas abscess. Physicians also need to sharpen their awareness of the potential malignant carcinomas mimicking psoas abscess.